Faktor - Faktor yang Berhubungan dengan Kecemasan Ibu Hamil Trimester III dalam Menghadapi Persalinan di UPT Puskesmas Pemulutan Tahun 2025 - Malita; Ratna Dewi; Sendy Pratiwi Ramadhani; Putu Lusita Nati Indriani (STIKes Budi Mulia Sriwijaya, 2025)
Pregnancy is a natural process that causes physiological and psychological changes throughout the pregnancy. Anxiety during pregnancy increases stress hormones that can disrupt blood flow to the uterus and weaken uterine muscle contractions, causing prolonged labor, so that the baby is also at risk of experiencing congenital abnormalities, prematurity, fetal distress, and behavioral and emotional disorders. This study aims to determine the relationship between therapeutic communication, work, and knowledge with anxiety in pregnant women in the third trimester of childbirth. This study was conducted at the Pemulutan Community Health Center in July 2025. This study used an analytical survey, quantitative cross-sectional design with a population of 126 respondents and a sample of 56 pregnant women in the third trimester with accidental sampling techniques, primary data types, questionnaire research instruments interview process.. The results of bivariate analysis obtained a significant relationship between therapeutic communication (0.002) <α (0.05), there was a significant relationship between work (0.000) <α (0.05), there was a significant relationship between knowledge (0.000) <α (0.05) with anxiety in pregnant women in the third trimester, there was a relationship between therapeutic communication, work and knowledge with anxiety in pregnant women in the third trimester in facing childbirth at the UPT Pemulutan Health Center, Ogan Ilir Regency. Implementing a holistic approach and empathetic therapeutic communication is expected to improve the quality of services and mental readiness of pregnant women.